Refractory Primary Mediastinal B-Cell Lymphoma: A Case Report of Conventional Chemotherapies, Immune Checkpoint Inhibitors, Polatuzumab Vedotin, Transplantation, and Post-Transplant Large Granular Lymphocytosis - Pincha, Rajat; Radhakrishnan, Vivek S.; Kumar, Jeevan; Nag, Arijit; Bhave, Saurabh Jayant; Zameer, Lateef; Vinarkar, Sushant S.; Das, Jayanta; Mishra, Deepak Kumar; Chandy, Mammen; Nair, Reena (Indian Journal of Medical and Paediatric Oncology, 2022)
We report a case of stage IV primary mediastinal B-cell lymphoma in a 27-year-old young woman, who was refractory and chemoresistant to frontline conventional rituximab-based intensive chemotherapy and subsequent lines of conventional and immune checkpoint inhibitor-based therapies. She was successfully treated using a polatuzumab-based regimen and consolidated with an allogeneic haploidentical hematopoietic stem cell transplantation. She developed post-transplant large granular lymphocytosis that was managed conservatively. She is now relapse-free, 600 days post-transplant. The management of this patient provided several teaching points in the use of different modalities of immunotherapies in a hard-to-treat cancer and its related conditions.
Keywords: primary mediastinal B-cell Lymphoma; relapsed refractory disease; chemoresistance; polatuzumab vedotin; haploidentical transplantation